An entangled cosmos: contextualising a close reading of a nineteenth-century |Xam San narrative - Lewis-Williams, J. D. (Southern African Humanities, 2020)
In attempting to interpret San rock art, researchers have drawn on the verbatim |Xam San manuscripts that Wilhelm Bleek and Lucy Lloyd compiled in the 1870s. One of the narratives preserved in that archive appears to identify ‘little girls’ as image-makers and also the pigments that the |Xam employed in the making of their rock paintings. The tale has, however, been misunderstood because of problems in translation. Properly understood, it provides invaluable insights into the shifting complexities and entanglement of terminal southern African Later Stone Age San thought, ritual, myth, daily material life and, indeed, the nature of the overall, if not specific, cognitive context in which the practice of image-making occurred. Detailed lexical analysis, rather than a broad structural analysis of the plot, reveals a context in which apparently different areas of belief and ritual interact and encase one another and so contribute to a fuller understanding of the kind of thinking and experiencing that characterised |Xam San mental and material life. KEY WORDS: San, Bleek, Lloyd, girls’ puberty, entanglement.